(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the artistic and scientific potential of the Turkic language as interpreted in the works of Alisher Navoi. It highlights Navoi’s decisive role in the formation and development of the Uzbek literary language, particularly through his treatise “Muhokamatu-l-lugʼatayn,” in which he demonstrated the equality of Turkic with Persian. The study analyzes Navoi’s contribution to the evolution of Uzbek poetry and focuses on the integration of Arabic and Persian lexical elements within the epic “Sabʼai Sayyor” from his “Khamsa.” Using comparative-analytical and historical-linguistic methods, the research explores semantic changes and stylistic functions of loanwords. The findings confirm that Navoi not only elevated the status of the Turkic language but also created a new poetic model that harmonized different linguistic traditions, laying a strong foundation for the future development of Uzbek literature.